BUILDING AND DEVELOPING A CREATIVE BUSINESS SPIRIT THAT IS BENEFICIAL TO SOCIETY THROUGH THE APPLICATION OF ENTREPRENEURSHIP - Maulidina Yuliani; Ritha F Dalimunthe; Prihatin Lumbanraja (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2024)
One of the factors that a country can say is advanced can be seen from the number of entrepreneurs in that country, the more entrepreneurs there are, the greater the hope that people can get jobs according to their skills, so that it can raise the standard of living of the people of a country, because it will create jobs and reduce the unemployment rate. . The aim of this research is to find out how to build a creative business spirit and apply the tradition of entrepreneurship, in the midst of economic attacks that are getting bigger every day and coupled with increasingly narrow job opportunities. Entrepreneurship is one of the most effective ways to revive economic development from small scale to become a driver of large-scale economic development. Society is required to be astute in seeing and taking advantage of existing opportunities to advance business in bringing about social change. Society hosted by the government still needs to prepare for the birth of entrepreneurs and build creative businesses that are more likely to bring positive change and help move the economy more quickly. This research uses the literature review method, literature review aims to solve problems. From the results of the literature review, we can draw the conclusion that family, education and government are three traditions that are able to build the application of entrepreneurship in society.